The effects of continuous chest compression protocol on cardiopulmonary resuscitation (CPR) quality and fatigue - Katie J. Lyman; Thomas A. Hanson; Jennifer A. Longo (PLoS ONE, 2026)
Aim This study investigated how fatigue (measured both subjectively and objectively) and cardiopulmonary resuscitation (CPR) quality are impacted by various CPR protocols, principally comparing continuous chest compressions with intermittent rest periods. Methods A sample of 23 participants (M = 22.3 years ± 3.8) was used in a cross-sectional design. Four compression:rest ratios were analyzed: 30:10, 50:10, 100:10, and continuous compressions (CC), with all participants performing CPR for 9 minutes in each condition. Subjective fatigue was measured using the Borg Rating of Perceived Exertion (RPE) at baseline, three, six, and nine minutes. Objective fatigue data were collected using the Parvo metabolic cart and heart rate (HR) monitors. Regression models of CPR performance quality (i.e., depth, recoil, and rate) investigated the effect of CPR protocol while controlling for participant variables. Fatigue (i.e., RPE, HR, and VO 2 ) were compared across CPR protocols using repeated measure one-way ANOVA and post hoc Tukey’s honestly significant difference (HSD) tests. Results Significant differences in performance were observed between CC and other protocols: 30 (p < .001), 50 (p = .009), and 100 (p = .031). Percent of full chest recoil was also significantly lower during CC than in 30, 50, and 100 conditions (all p < .001). Subjective fatigue increased significantly with longer compression ratios (p < .001). Conclusion Higher compression ratios result in greater perceived fatigue and reduced CPR performance quality. Rescuer fatigue should be considered in CPR protocol design to optimize both rescuer effectiveness and patient outcomes.